The Unhappy Conduit: GI and Surgical Problems Post Esophagectomy: Surgical Perspective. Issue 2 (June 2022) - Azari, Feredun; Kennedy, Gregory T.; Dempsey, Daniel T.
Operations for esophageal and proximal gastric cancers are increasing. The most common surgical intervention performed for this patient population is esophagectomy. Regardless of the technical approach pursued, creation of a neo-esophageal conduit imposes various anatomic and physiologic challenges. These patients often undergo additional endoscopic and surgical revision procedures to improve their quality of life. Some of the most common complications encountered by medical professionals managing these challenging patients include para-conduit hiatal hernias, acid and biliary reflux, and redundant or dysfunctional neo-esophageal conduit. As survival and long-term outcomes improve, clinicians are encountering novel complications including conduit neoplasia and tracheal conduit fistulas. This review highlights some of the common complications post esophagectomy with focus on initial diagnosis and management strategies.